Positive selection acting on splicing motifs reflects compensatory evolution - Ke, Shengdong; Zhang, Xiang H.-F.; Chasin, Lawrence A. (Genome Research, 2008)
We have used comparative genomics to characterize the evolutionary behavior of predicted splicing regulatory motifs. Using base substitution rates in intronic regions as a calibrator for neutral change, we found a strong avoidance of synonymous substitutions that disrupt predicted exonic splicing enhancers or create predicted exonic splicing silencers. These results attest to the functionality of the hexameric motif set used and suggest that they are subject to purifying selection. We also found that synonymous substitutions in constitutive exons tend to create exonic splicing enhancers and to disrupt exonic splicing silencers, implying positive selection for these splicing promoting events. We present evidence that this positive selection is the result of splicing-positive events compensating for splicing-negative events as well as for mutations that weaken splice-site sequences. Such compensatory events include nonsynonymous mutations, synonymous mutations, and mutations at splice sites. Compensation was also seen from the fact that orthologous exons tend to maintain the same number of predicted splicing motifs. Our data fit a splicing compensation model of exon evolution, in which selection for splicing-positive mutations takes place to counter the effect of an ongoing splicing-negative mutational process, with the exon as a whole being conserved as a unit of splicing. In the course of this analysis, we observed that synonymous positions in general are conserved relative to intronic sequences, suggesting that messenger RNA molecules are rich in sequence information for functions beyond protein coding and splicing.
10.1101/gr.070268.107